Measurements of a heated low speed channel - Huang, Andy Zi Jie. (2010)
In this project, measurements are done in a heated low speed channel to simulate the actual scenario in a laptop. The purpose of the experiment is to investigate how heat is transferred from a congested space with low air velocity. By studying and understanding the heat transfer patterns, methods could be invented and created to provide a more reliable and efficient cooling in the compact space of a heated laptop. In a forced convection process, convection currents are formed due to the differences in the air densities at different temperatures, causing a series of high and low velocities along the y-direction as shown in Figure 6.1. When air is flowing at different velocities in the tunnel, it will cause a difference in temperatures along the y-direction which depicts the convection rolls. To aid in the investigation, the densely packed internal of a laptop is simulated by a return flow test rig with heating facility. The low air velocity inside the wind tunnel of the test rig will be controlled and kept constant by a pulse width modulation circuit. For calibration, a conveyor belt system is designed and constructed to calibrate the hot-wire for low velocity measurement in the range of 10 to 100 mm/s whereas the yaw angle calibration is used to calibrate the effective angle of the cross-wire for the measurements of u and v velocity components in the x-y plane and u and w velocity components in the x-z plane. For a further and more in depth investigation, a cold-wire is used to take the temperature of each sections of the channel under different heating conditions. The results of the experiments will provide a better understanding on the formation of convection rolls under different heating conditions in a low air velocity channel and thus, leading to the improvisation of the current laptop designs for a more effective performance.